Advanced Technologies for the Bonding and De-Bonding of Armour Structures (ArmourBond) - Chatzikypraios, Konstantinos (Cranfield University, 2019)
A common multilayer vehicular armour design consists of a combination of adhesively-bonded metallic, ceramic and composite layers. The different properties of each layer contribute in fulfilling the lightweight and the high ballistic property requirements of these structures. Due to their complexity, though, there still are limitations in their performance that are not fully understood. These limitations are associated with a lack in understanding and controlling the propagation of the stress waves, which are induced by the projectile upon the impact event, through the different layers. The stress wave propagation, via reflection and transmission phenomena, is controlled by the acoustic impedance mismatch between the layers. The current epoxide-based armour systems, are incapable of attenuating the stress waves, promoting stress transmission, and exposing the occupants of the vehicles to greatly damaging shocks. Additionally, an increased reflection of the stress waves (in the form of tensile stress) causes the ceramic failure. As a result, the multi-hit performance of the armour is degraded. This PhD study will try to overcome these limitations by focusing on the investigation of novel adhesively-bonded systems, of high energy absorbance capability and improved shock wave attenuation, enhancing the multi-hit capability of the armour. The effect of the material selection and surface treatment on the adhesion and on the mechanical and ballistic performance of the novel structures (using the Split Hopkinson Pressure Bar and the Gas Gun apparatus) will be thoroughly investigated. Further to the above, the controlled debonding of these structures (dismantlable adhesion) will be also investigated, with respect to tailoring the armour against specific threats, fulfilling the “fly light and fight heavy” concept. Finally, the upscaling of the developed materials and structures will take place so that novel armour packs can be tested and validated, according to the STANAG standards.
Keywords: 'High strain rate testing'; 'SHPB'; 'Armour structures'; 'DSDS19 Poster'; 'DSDS19'; 'Materials Engineering not elsewhere classified'; 'Composite and Hybrid Materials'